Greening steel work: Varieties of Capitalism and the 'greening' of skills. Issue 3 (2nd April 2016) - Evans, Claire; Stroud, Dean
Abstract : An important driver of change in work, employment and skills is European Union policy aims of sustainable economic growth and the cultivation of a green economy. Part of the latter – which is supported by increasing environmental regulation – focuses on the development of a 'green skills agenda', which involves the 'greening' of existing occupations as well as meeting the skill needs of new environmental sectors and occupations. In this paper, we compare attempts to 'green' work and skills through an examination of engineering apprenticeships within the German and British steel industries. We argue that efforts to 'green' skills are taking place at varying degrees of intensity, mostly because of variations in institutional context. The evidence we present suggests that implementation of change is much more dynamic in the context of Coordinated Market Economies such as Germany, where development is shaped by robust VET frameworks and wider processes of environmental innovation. In contrast, within Liberal Market Economies such as the UK, there are significant barriers to the vision for and investments in skills generally, as well as those necessary for greening the labour process, with an extant development paradigm that is driven by short-term benefits and a limited focus on environmental compliance.